The curse and blessing of training the unemployed in a changing economy: the case of East Germany after unification - Michael Lechner; Ruth Miquel; Conny Wunsch (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
We analyse the effects of public sector sponsored training for the unemployed in the transition process in East Germany. For the microeconometric analysis, we use a new, large and informative administrative database that allows us to use matching methods to reduce potential selection bias, disaggregate programme types, and to observe interesting labour market outcomes over 8 years. We find that, generally, all training programmes under investigation increase long-term employment prospects and earnings. However, as an important exception, the longer training programmes are on average not helpful for their male participants. At least part of the explanation for this negative result is that caseworkers severely misjudged the structure of the future demand for skills.
Keywords: J68; 330; IAB-Beschäftigtenstichprobe; prozessproduzierte Daten; Umschulung - Erfolgskontrolle; Weiterbildungsförderung - Erfolgskontrolle; Beschäftigungseffekte; Teilnehmer; berufliche Reintegration; Lohnentwicklung; Arbeitslose; arbeitslose Männer; Ostdeutschland; Bundesrepublik Deutschland; Arbeitsmarktpolitik; Weiterbildung; Geschlecht; Arbeitslosigkeit; Panel; Neue Bundesländer